Optimizing quality assurance and service quality staff in improving guest satisfaction at hotels in Yogyakarta, Indonesia - Sekar Cahyaningrum; Imanuel Rizal Saputra; Kezia Tifa Aprilria (Borneo Novelty Publishing, 2024)
Purpose - The purpose of this paper is to determine the role of quality assurance in increasing guest satisfaction at Hotel in Yogyakarta. The study emphasizes the importance of quality assurance in the hospitality industry as a key factor in improving guest satisfaction.Methodology/Design/Approach - The study uses the literature study method, collecting and analyzing various reference sources such as journals and books related to quality assurance in the hospitality industry.Finding - The literature study reveals that quality assurance plays a crucial role in enhancing guest satisfaction. By ensuring consistent service and standards, quality assurance directly impacts guest experiences and contributes to the hotel's reputation.Originality/Value - This research underscores the importance of maintaining high-quality standards in hotel operations, highlighting how quality assurance practices can significantly improve guest satisfaction and, in turn, the overall reputation of the hotel.